Digitalisasi Media Promosi Di Cv. Muara Rahmat - Aditama, Krisna Prayoga; ., Taufikurrahman (CV. ITTC INDONESIA, 2026)
The digitalization of promotional media has become a strategic necessity for small and medium-sized enterprises (SMEs) amid rapid technological advancements. The main issue faced by CV. Muara Rahmat is the suboptimal utilization of digital promotional media due to the absence of an official website as a central digital identity, resulting in company information being dispersed across social media platforms that are temporary and not integrated. This gap has caused digital promotion activities to be unsystematic and unsustainable. This study aims to analyze and implement the digitalization of promotional media through the development of a company profile website for CV. Muara Rahmat. The research employs a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The results indicate that the developed website is able to present company information, business units, galleries, and contact details in a structured and professional manner, functioning as a digital hub that supports integration with social media. Functional testing using the black box testing method confirms that all main features operate as designed. The study concludes that the development of a company profile website plays an important role as a foundation for the digitalization of SME promotional media, enhancing professionalism, credibility, and the long-term effectiveness of CV. Muara Rahmat’s digital promotion strategy.